Palaeodirectional and palaeointensity results of Paleocene and Eocene basalts from West Greenland (Dataset) ... - Riisager, Janna; Perrin, Mireille (Magnetics Information Consortium (MagIC), 2022)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeodirectional and palaeointensity results of Paleocene and Eocene basalts from West Greenland ...